Teori Konvergensi dalam Perspektif Pendidikan Islam: Integrasi Faktor Lingkungan dan Pembawaan dalam Pembentukan Karakter Peserta Didik - Sepiyah Sepiyah (STAI AL-AMIN, 2026)
Character building is a fundamental objective of Islamic education. The classical debate on innate factors (nature) and environmental influences (nurture) in human development has led to the emergence of Convergence Theory, which emphasizes the integration of both aspects. This article aims to examine Convergence Theory from the perspective of Islamic education and analyze its relevance to students’ character formation. This study employs a qualitative approach using library research methods, analyzing educational psychology literature alongside primary Islamic sources such as the Qur’an, Hadith, and classical Muslim scholars’ thoughts. The findings indicate that the Islamic concept of fitrah aligns with the notion of innate potential, while educational environments family, school, and society play a strategic role in guiding and developing this potential. Integrating Convergence Theory into Islamic education underscores the importance of synergy between innate dispositions and a structured educational environment to develop students with strong faith, noble character, and balanced personalities. Keywords : Convergence Theory, Islamic Education, Fitrah, Environment, Character Education.